HUMAN RESOURCE MANAGEMENT – GLOBAL ECONOMY IMPORTANT FACTOR. IMPLEMENTATION OF MODERN SYSTEMS OF LABOR RESOURCE MANAGEMENT - Ergasheva Shakhzoda Murodbek kizi (Journals Park Publishing, 2023)
This article examines the opinions of foreign and domestic scientists on the introduction of a modern system of human resources management. Also, the essence of the stages of evolutionary approaches to human resources management, the tasks of introducing a modern management system and ways to solve them are highlighted.
Keywords: Human resource management, human resource management system, principles of human resource management, personnel, digital HR.